A competency evaluation method of human resources managers based on multi-granularity linguistic variables and VIKOR method - Liu, Peide; Wu, Xingying (Technological and Economic Development of Economy, 2012)
According to the characteristics of human resources managers’ competency and the research of relevant literatures at home and abroad, a competency evaluation method of human resources managers based on multi-granularity linguistic variables and VIKOR method is proposed. Firstly, the evaluation indicator system based on the competency of human resources managers is constructed. Then, by converting the evaluation information of different experts in different granularity to the same granularity by two-semantics, the comprehensive evaluation values can be obtained by integrating information of different experts. Further, the objective weights of the evaluation indexes were determined by the entropy method and an evaluation method were proposed based on the VIKOR method. Finally, an application example is given to illustrate the evaluation procedures of the developed approach and to demonstrate their practicality and effectiveness.